1998
DOI: 10.1021/jp983520d
|View full text |Cite
|
Sign up to set email alerts
|

Optical Absorption of Solvated Electrons in Water and Tetrahydrofuran/Water Mixtures

Abstract: In the past Jou and Dorfman (J. Chem. Phys. 1973, 58, 4715) have determined the optical absorption spectra of solvated electrons (esolv -) in binary mixtures of tetrahydrofuran (THF) and water over the entire concentration range. From these experiments they concluded that the position of the absorption maximum and the width at half-height of the band are dominated by water. By additional experiments we show that at least for some mixtures with a mole fraction X(THF) ≤ 0.50, we obtain spectra at 298 K which agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 37 publications
3
34
0
Order By: Relevance
“…Hertwig, Hippler and Unterreiner [24] demonstrated that the spectrum of the relaxing hydrated electron is blue-shifted during this process with a time constant τ ϭ 300Ϯ50 fs. The assumptions for the simple evaluation of the experimental observations are: The oscillator strength is 1 and the spectra show shape stability [9,25,26]. This observation sustains our former suggestion [22].…”
Section: Some Comments On the 'Incompletely Relaxed Electron'supporting
confidence: 83%
See 2 more Smart Citations
“…Hertwig, Hippler and Unterreiner [24] demonstrated that the spectrum of the relaxing hydrated electron is blue-shifted during this process with a time constant τ ϭ 300Ϯ50 fs. The assumptions for the simple evaluation of the experimental observations are: The oscillator strength is 1 and the spectra show shape stability [9,25,26]. This observation sustains our former suggestion [22].…”
Section: Some Comments On the 'Incompletely Relaxed Electron'supporting
confidence: 83%
“…However, up to now it is difficult to calculate the optical spectra with these methods (for a critical comparison between theory and experiment see [9]). Therefore, it is suggested that there are Brought to you by | The University of Auckland Library Authenticated Download Date | 6/22/15 3:30 AM similar problems with the simulation of correlation functions like the displacement correlation function (Eq.…”
Section: Comparison Of Experimental Results With Quantum-statistical mentioning
confidence: 99%
See 1 more Smart Citation
“…[22,23] In this case, and for am olar fraction of THF lower than 0.49, the presence of THF only slightly changed the spectrum of the solvated electron, which was similar to the spectrum of the solvated electron in water,b ut at ah igher temperature. [23] In our case, the transients pectrum we measured (for am olar fraction of DEC equal to 0.43) is similart ot hat obtained in EC, butr edshifted ( Figure 2). In contrast with the measurements performed for THF/water mixtures, forw hich the time-resolveds pectra exhibited isosbestic points andt he hydration dynamicsw as describedb yt wo-state kinetics, which implied thatn anometer inhomogeneities exist in these mixtures, no such trend was observed here (Figure 1c), which suggests that the EC/DEC mixture is homogeneous even at the [24] The band of the solvated electron in EC/ DEC is broader than that measured in neat EC, as clearly shown by the spectrum measured2 0psa fter the electron pulse ( Figure 2).…”
Section: Picosecond-pulse Radiolysis Experiments With Ec Dec and 50supporting
confidence: 57%
“…We note that the spectral broadening in the presence of high-concentration metallic salt is still an arguable subject. 39,45,56 Bonin et al 45 and Marbach et al 56 claimed the spectral stability of the absorption spectrum of solvated electrons observed in concentrated salt solutions in water or in mixtures of THF/water by laser photolysis experiments, while Kreitus 39 reported a spectral broadening with increasing LiCl concentration by pulse radiolysis measurements.…”
Section: Resultsmentioning
confidence: 99%